1989
DOI: 10.1172/jci113871
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen-independent platelet adhesion and thrombus formation on subendothelium mediated by glycoprotein IIb-IIIa complex at high shear rate.

Abstract: Platelet adhesion and thrombus formation on subendothelium, studied at a shear rate of 2,600 s'l, were inhibited by two synthetic peptides known to interact with GPIIb-IIIa. One peptide (HHLGGAKQAGDV) corresponds to the carboxyl terminal segment of the fibrinogen y-chain ('y400411) and the other (RGDS) contains the amino acid sequence Arg-Gly-Asp (RGD) common to fibronectin, von Willebrand factor, vitronectin and the a-chain of fibrinogen. Neither platelet adhesion nor thrombus formation were decreased in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
101
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(109 citation statements)
references
References 77 publications
(34 reference statements)
7
101
0
1
Order By: Relevance
“…These non-receptor tyrosine kinases play a critical role in integrin signal transduction but are not essential for soluble agonist-induced calcium flux (21). 2 Finally, the demonstration that PLC␥2 Ϫ/Ϫ mouse platelets have a defective calcium response during platelet adhesion to fibrinogen is consistent with its previously defined role in adhesion receptor signal transduction (40). FIG.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…These non-receptor tyrosine kinases play a critical role in integrin signal transduction but are not essential for soluble agonist-induced calcium flux (21). 2 Finally, the demonstration that PLC␥2 Ϫ/Ϫ mouse platelets have a defective calcium response during platelet adhesion to fibrinogen is consistent with its previously defined role in adhesion receptor signal transduction (40). FIG.…”
Section: Discussionsupporting
confidence: 53%
“…2 Third, the cytosolic calcium response was strictly dependent on Src kinases. These non-receptor tyrosine kinases play a critical role in integrin signal transduction but are not essential for soluble agonist-induced calcium flux (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The continued ability of ADP to induce aggregation of PRP from the PG-1 F(ab') 2 -treated animals suggests that the reduction of thrombus formation in these animals is not mediated by inhibition of fibrinogen binding to platelet GPIIb/IIIa. In the case of human platelets, Weiss and coworkers 5 have recently demonstrated that other adhesive ligands such as vWF, vitronectin, or fibronectin may be involved in platelet adhesion and thrombus formation on subendothelium when studied at high shear rates. Whether such ligands may contribute to hemostasis in the guinea pig by binding to guinea pig platelet GPIIb/ Ilia is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mature VWF comprises a series of multimers from 500 kD to over 10 000 kD (Chopek et al, 1986), the larger multimers most effectively promoting platelet adhesion (Meyer & Girma, 1993). Two platelet receptors have been shown to bind VWF, glycoprotein (GP) Ib involved in primary adhesion, and GPIIb/IIIa which plays a major role in the subsequent steps of platelet spreading and aggregation Baumgartner et al, 1980;Sakariassen et al, 1986;Ruggeri & Zimmerman, 1987;Weiss et al, 1989;Savage et al, 1992). Platelets do not bind soluble VWF in the absence of high shear forces.…”
mentioning
confidence: 99%